Magnitude of preterm hospital neonatal mortality and associated factors in northern Ethiopia: a cross-sectional study - Bekahegn Girma; Jemberu Nigussie (BMJ Open)
Objective This study aimed to assess the magnitude of preterm neonatal mortality in hospitals and associated factors in northern Ethiopia.Design Institutional-based cross-sectional study.Setting Comprehensive specialised hospitals in the Tigray region, northern Ethiopia.Participants Preterm neonates admitted in Ayder and Aksum comprehensive specialised hospitalsPrimary outcome Magnitude of preterm neonatal mortality.Secondary outcome Factors associated with preterm neonatal mortalityResult This study was conducted from 1 April 2019 to 15 May 2019 among 336 participants with a response rate of 96.8%. The magnitude of preterm neonatal mortality was 28.6% (95% CI: 24.0 to 33.7). In multivariable logistic regression, respiratory distress syndrome (adjusted odd ratio (AOR)=2.85; 95% CI: 1.35 to 6.00), apnoea of prematurity (AOR=5.45; 95% CI: 1.32 to 22.5), nulli parity (AOR=3.63; 95% CI: 1.59 to 8.24) and grand parity (AOR=3.21; 95% CI: 1.04 to 9.94) were significant factors associated with preterm neonatal mortality. However, receiving Kangaroo mother care (AOR=0.08; 95% CI: 0.03 to 0.20) and feeding initiated during hospitalisation (AOR=0.07; 95% CI: 0.03 to 0.15) were protective against preterm neonatal mortality.Conclusions The magnitude of preterm neonatal mortality in hospitals was still high. Interventions geared towards curbing preterm in-hospital neonatal mortality should strengthen early diagnosis and treatment of preterm newborns with respiratory distress syndrome and apnoea of prematurity; while concomitantly reinforcing the implementation of kangaroo care and early feeding initiation is important.